Transformation of Islamic Education in Facing the Challenges of Extremism in the Digital Era - Suhendi, Saca (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
The development of digital technology has created significant social changes in the lives of young Muslim generations. Interactions formed through social media and digital religious figures have also shifted religious authority from what was previously formal. In this situation, Islamic education faces a major challenge in protecting students from the influence of ideological extremism that is developing through digital platforms. This study aims to examine how Islamic education can transform to answer the challenges of extremism in the digital era. This study uses a qualitative approach by utilizing data from various relevant literature sources. The analysis was carried out descriptively and qualitatively to reveal the relationship between digital social dynamics and students' ideological resilience. The results of the study indicate that there is an urgent need to update the curriculum, methods, and ecosystem of Islamic education to be more responsive to rapidly changing social realities. The role of teachers, families, communities, and policies that support moderate Islamic education are key elements in efforts to prevent radicalization. With a collaborative and reflective approach, Islamic education has a great opportunity to form a generation of Muslims who are critical, tolerant, and resistant to extreme ideologies.